The Effect of the Adaptive Mentality “MANTAP” Program on Resilience and Stress Levels in Nursing Students: A Quasi-Experimental Study - Amaliyah, Eli; Sulastri, Tuti; Puspasari, Ike (Journal of Health and Nutrition Research, 2025)
The "MANTAP" (Adaptive Mentality) program as a management strategy can strengthen the resilience of students studying at Sultan Ageng Tirtayasa University. This study was conducted using a quasi-experimental design with two control groups and an intervention group by conducting pre- and post-tests on students of the Nursing Department, Faculty of Medicine, Sultan Ageng Tirtayasa University-Banten. Data were collected at baseline, immediately post-intervention, and at a two-month follow-up. The MANTAP (Adaptive Mentality) Program intervention was carried out for one month. The total sample recruited was 120 in the control group and 120 in the intervention group. Bivariate analysis using paired t-tests was. Data was processed using SPSS version 22. Statistically detectable differences were observed (p < .001). Average stress levels decreased in both groups, with a greater reduction in the intervention group (from 11.71 to 7.16) compared to the control group (from 10.52 to 9.39), indicating a stronger effect of the intervention. Meanwhile, the average resilience level showed a slight increase in the control group (from 84.11 to 84.31), while the intervention group experienced a substantial improvement (from 81.81 to 91.23), confirming the intervention's effectiveness in enhancing students' psychological resilience. Resilience or mental toughness helps students recover from difficulties and adapt to academic pressure. Appropriate psychological interventions can reduce stress levels and increase students' mental toughness. The application “MANTAP” (Adaptive Mentality) program can be programmed as a management strategy to strengthen the resilience of nursing students.